Coaching With Artificial Intelligence: Concepts and Capabilities. (March 2021) - Graßmann, Carolin; Schermuly, Carsten C.
Artificial intelligence (AI) has brought rapid innovations in recent years, transforming both business and society. This paper offers a new perspective on whether, and how, AI can be employed in coaching as a key HRD tool. We provide a definition of the concept of AI coaching and differentiate it from related concepts. We also challenge the assumption that AI coaching is feasible by challenging its capability to lead through a systematic coaching process and to establish a working alliance to clients. Based on these evaluations, AI coaching seems to encounter the greatest difficulties in the clients' problem identification and in delivering individual feedback, which may limit its effectiveness. However, AI generally appears capable of guiding clients through many steps in the coaching process and establishing working alliances. We offer specific recommendations for HRD professionals and organizations, coaches, and developers of AI coaching programs on how AI coaching can contribute to enhance coaching practice. Combined with its lower costs and wider target group, AI coaching will likely transform the coaching profession and provide a future HRD tool.